Reduced expression of Rho guanine nucleotide dissociation inhibitor-α modulates the cytotoxic effect of busulfan in HEK293 cells - Reimer, Janka; Bien, Sandra; Sonnemann, Jürgen; Beck, James F.; Wieland, Thomas; Kroemer, Heyo K.; Ritter, Christoph A. (Anti-cancer drugs, 2007)
High-dose busulfan is an important component in many conditioning protocols for hematopoietic stem cell or bone marrow transplantation. Treatment with busulfan results in the inhibition of cell cycle progression and apoptosis of tumor cells. As Rho GTPases are involved in cell cycle regulation, we investigated the influence of modified Rho guanine nucleotide dissociation inhibitor-α (GDI), a physiological inhibitor of Rho GTPases, on busulfan activity in cancer cells. RhoGDIα has been shown to be overexpressed in multiple types of tumors such as ovarian and breast cancer. To investigate the role of RhoGDIα, we established a RhoGDIα knockdown by the transient transfection of HEK293 cells with specific small interfering RNA resulting in strongly reduced RhoGDIα mRNA and protein expression. Other members of the RhoGDI family such as RhoGDIβ and RhoGDIγ were not affected. In RhoGDIα knockdown cells, cell cycle regulation was not altered by the downregulation of RhoGDIα; however, the rate of apoptotic cells increased when compared with the control small interfering RNA-transfected cells. In addition, treatment of cells with busulfan resulted in a further increased apoptotic rate, as determined by fluorescence-activated cell sorter analysis and caspase-3 activation. Such a sensitization of RhoGDIα small interfering RNA transfected cells was also found upon treatment with doxorubicin and taxol. In summary, we could demonstrate that the expression of RhoGDIα influences the sensitivity of cells toward busulfan-induced cytotoxicity.